Professional standards for after school hours care in Australia. (December 2020) - Cartmel, Jennifer; Brannelly, Kylie; Phillips, Andrea; Hurst, Bruce
Highlights: Professionalism of Outside School Hours Care (OSHC) Workforce. Professional Standards for OSHC educators. Evaluation of professional development using Guskey (2016). Time and finances of OSHC services impacted on the intent of the professional development. Abstract: The Outside School Hours Care (OSHC) sector is the fastest growing child care sector in Australia. It is staffed by a workforce that is an eclectic mixture of disciplines. In policy and public perception the workforce has been often linked inappropriately to the workforce of very young children. Queensland Children's Activities Network (QCAN) developed a set of professional standards (The Standards) for educators working in OSHC. The Standards reflect and build on national and international evidence that an educator's effectiveness has a powerful impact on children's development and wellbeing. The Standards were introduced to the OSHC sector with a professional development program. A five level model of evaluation (Guskey, 2016) is being used to provide a systemic evaluation of the professional learning associated with the Standards. This paper discusses some of the findings associated with the levels one and two of the evaluation.